Challenges and Solutions Related to Hunting Sport in Jordan from the Jordanian Drafting Point of View - Ali Abdumajeed Zureigat, Ayed (Dirasat: Human and Social Sciences, 2022)
The study aimed to identify the level of challenges facing the sport of hunting from the point of view of Jordanian hunters as well as the proposed solutions to those challenges, and to achieve this, the researcher used the descriptive approach on a sample consisting of (n = 133) hunters. To reduce face-to-face interaction, an (open) electronic questionnaire was built using (Google questionnaire), which consisted of (two questions) that addressed the challenges facing the sport of hunting and the proposed solutions from their point of view. Then the researcher worked with the Delphi method, which is building a new questionnaire based on the answers of the study sample on the open questionnaire for the most frequent paragraphs with the five- Answers Likert responses ladder and redirecting them again to the sample. It consisted of (57) paragraphs. The challenges dealt with (26) paragraphs. In addition, the proposed solutions (31) paragraphs. To treat the data statistically, the researcher used means, standard deviations, and the Cronbach Alpha equation. The results of the study showed that the level of challenges was high for the study sample with an average of (4.44), The most important challenge is that the study sample was (limited hunting grounds) and the average of the proposed solutions was high with an average of (4.57). It was the most important solution for establishing hunting resorts to attract tourism.